STUDY ON REAL AND FORMAL SOURCES OF LAW - Mircea TUTUNARU (Challenges of the Knowledge Society)
The right switch first factual existence of the form, a fact that gives him the opportunity to be known and, consequently, to be respected and applied to the specific case. These specific ways of expressing the content of the law in legal theory and legal sciences branch of law called the source or sources of law. The concept of source of law is the ideological source and meaning in the sense of legal civilization pool connects to a national legal system.